Bedside cerebral microvascular imaging of patients with disorders of consciousness: a feasibility study - Qianqian Ge; Lijie Huang; Qiang Fu; Shuai Han; Rui Wang; Jianghong He; Changhui Li; Changhui Li; Jianwen Luo; Long Xu (Frontiers in Neuroscience)
BackgroundEfficient bedside neurofunctional monitoring is crucial for managing disorders of consciousness (DoC). Ultrafast Power Doppler Imaging (uPDI) outperforms traditional Ultrasound in bedside for assessing the microcirculatory system. However, intracranial blood flow imaging traditionally faces limitations due to the skull’s impedance. This constraint is circumvented in common post-craniectomy DoC patients, who present a unique observational window for uPDI.MethodsWe conducted uPDI scans on five DoC patients of different ages and consciousness levels who had undergone decompressive craniectomy. We compared the imaging results from uPDI with traditional PDI and identified the physiological and pathological conditions with uPDI.ResultsDetailed microvascular images of both cortical and subcortical areas were obtained using uPDI through the craniectomy window. Notably, uPDI demonstrates high sensitivity and imaging depth, revealing microvessels as small as 320 μm in diameter at 4 cm depth, and detecting blood flow signals up to 6 cm beneath the scalp.ConclusionThrough the decompressive cranial windows of DoC patients, we obtained cerebral microvascular images with significantly higher sensitivity without the need for contrast agents.SignificanceOur research provides a novel bedside cerebral microcirculation imaging method for patients with DoC, offering convenient neurofunctional assessment to improve the clinical management of DoC patients.